PENGARUH ZIS, KEMISKINAN DAN HARAPAN LAMA SEKOLAH TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI JAWA BARAT - Finantyo Eddy Wibowo; Aang Gunaepi (UNIVERSITAS ISLAM SYEKH YUSUF, 2021)
The purpose of this study was to determine the effect of ZIS distribution, poverty, expected years of schooling on the Human Development Index in in the province of West Java. The research method used is panel data regression. This study uses data objects as many as 9 cities in West Java province. The results showed that poverty has a significant effect on Human Development Index, while other variables such as ZIS and expected years of schooling have an effect but are not significant. Panel data regression together between the variables ZIS, poverty and expected years of schooling shows that it has an influence on Human Development Index. Keyword : ZIS, Poverty, expected years of schooling, Human Development Index